Insights into the Efficacy of GLP-1 Agonists and Dual Agonists: Semaglutide and Tirzepatide in Obesity and Type 2 Diabetes - Opalska, Laura; Muciek, Adrianna; Mocarska, Martyna; Orłowska, Anna; Strakowska, Katarzyna; Maryńczak, Anna; Mencel, Jan; Nitschke, Nicole (Quality in Sport, 2024)
The increasing global prevalence of obesity and type 2 diabetes (T2D) has prompted significant advancements in pharmacological treatments, with glucagon-like peptide-1 (GLP-1) receptor agonists and dual agonists representing key innovations. Semaglutide, a GLP-1 receptor agonist, and tirzepatide, a novel dual agonist targeting both GLP-1 and glucose-dependent insulinotropic peptide (GIP) receptors, have shown remarkable efficacy in improving glycemic control and promoting weight loss. This review synthesizes the latest clinical evidence on the efficacy and safety of semaglutide and tirzepatide in the management of obesity and T2D, highlighting the findings from recent pivotal trials. In patients with T2D, semaglutide has consistently demonstrated superior glycemic control and weight loss compared to traditional therapies, as evidenced by the SUSTAIN trials [1]. Similarly, tirzepatide has emerged as a more efficacious option, with the SURPASS trials demonstrating greater reductions in HbA1c and more substantial weight loss compared to semaglutide. This positions tirzepatide as a potential first-line therapy for T2D.[2]. Both therapies have shown a favorable safety profile, with gastrointestinal side effects being the most common, and cardiovascular benefits observed in both drug classes. Given their dual mechanism of action, tirzepatide has shown unique potential in addressing both glycemic control and obesity, with emerging evidence supporting its use in non-diabetic patients with obesity [3].This review highlights the potential of these agents to revolutionise the management of obesity and T2D, with tirzepatide emerging as a promising next-generation treatment for metabolic diseases.